Social Media Marketing Dominates 2019 Research Trends: Pemasaran Media Sosial Mendominasi Tren Riset 2019 - Ghafiansya, Firdan Isya; Afifah, Jihan Alifia; Berlina, Yusita Setya; Abadi , Totok Wahyu (House of Wisdom: Journal on Library and Information Sciences, 2024)
This study investigates publication trends on the use of technology and social media in marketing strategies from 2013 to 2023 using Crossref index data and VOSviewer software. Data from scientific articles indexed by Crossref were collected using Publish or Perish (PoP) software and analyzed for keyword mapping. Results showed that 2019 had the highest number of publications, with "social media marketing" being the most common term. Authors (Ahrholdt, Dennis), (Greve, Geotz), and (Hopf, Gregor) were the most collaborative. Seven keyword clusters and four author keyword clusters were identified. The study emphasizes the need for a broader range of keywords to enhance research diversity and comprehensiveness, highlighting significant implications for optimizing marketing strategies through technological and social media advancements. Highlights: Publication Trends: Highest number in 2019 with 42 publications. Common Term: "Social media marketing" appeared 231 times. Collaborative Authors: (Ahrholdt, Dennis), (Greve, Geotz), (Hopf, Gregor) each had 10 links. Keywords: Technology, Social Media, Marketing Strategies, Crossref, VOSviewer